TANGGUNG JAWAB PELAKU USAHA TRAVEL TERHADAP PERBUATAN MELAWAN HUKUM YANG DILAKUKAN OLEH SUPIR - Rahman, Danang Sugandi; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Article 1367 Civil Code which states explicitly that "a person shall not only be liable for damages caused by his own act of neglecting also for damages caused by the deeds of those who are his responsibility or caused by goods under his control". In this work agreement does not explain in detail about the rights and obligations of the first party and the second party and more burdensome to the driver of the CV. Pasir Intan Travel. And what if the occurrence of traffic accidents accidents provided by the CV. Pasir Intan Travel compensation loss is not as expected. So this will be a polemic in society because there is no basis in providing the amount of compensation suffered by the victims of traffic accidents.This research uses obsevarsional reaserch method, by survey, that is collecting data in the form of questionnaire and interview to respondent in research location. While the nature of the research is descriptive that aims to provide a clear picture of the problems in the perusal.Legal relationship between travel service company CV. Sand Intan Travel and Driver rider car travel services CV. Pasir Intan Travel is a partnership to do the work in the form of travel services. The legal relationship was born from the agreement between the company's travel services CV. Pasir Intan Travel and driver as the driver of the car, which raises the bond in the form of rights and obligations between travel business actors with drivers based on employment agreement.Keywords : Responsiability – Businessman – Compensation